2013
DOI: 10.15580/gjiics.2013.1.110512229
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Services of Public Libraries in Meeting the Information Needs of Post-Secondary School Students in Some Three Selected Public Libraries in Nigeria

Abstract: The role of Public Libraries in meeting the information needs of the Community cannot be neglected. The Library is meant to serve the needs of all and sundry in the society without any bias. The main objective of this study was to examine the services of the Public Libraries in meeting the information needs of Post Secondary School Students in Public Libraries in Nigeria. The study adopted a Descriptive Survey Design and the Simple Random Sampling Techniques was used to select one hundred and fifty respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…As regards the information services, studies from Nigeria by Omopupa (2006), Ebiwolate (2010), Saleh and Lasisi (2011), Enemute and Okorodudu (2012), Oyeronke (2012), Akinola et al (2013), Chinwe et al (2014), Joy and Idowu (2014) and Obasi (2015) revealed that public library and information services generally revolve around reference services, storytelling services, film show services, career information services, online Internet services, lending services and photocopying services. Others include telephone, recreational and advisory services, current awareness, selective dissemination of information, bookmobiles, referral services, translation services, outreach and extension services, adult literacy programmes, audiovisual services, packaging and repackaging of information services and many more.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…As regards the information services, studies from Nigeria by Omopupa (2006), Ebiwolate (2010), Saleh and Lasisi (2011), Enemute and Okorodudu (2012), Oyeronke (2012), Akinola et al (2013), Chinwe et al (2014), Joy and Idowu (2014) and Obasi (2015) revealed that public library and information services generally revolve around reference services, storytelling services, film show services, career information services, online Internet services, lending services and photocopying services. Others include telephone, recreational and advisory services, current awareness, selective dissemination of information, bookmobiles, referral services, translation services, outreach and extension services, adult literacy programmes, audiovisual services, packaging and repackaging of information services and many more.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In Nigeria, studies by Omopupa (2006), Ebiwolate (2010), Saleh and Lasisi (2011), Enemute and Okorodudu (2012), Oyeronke (2012), Akinola et al (2013), Chinwe et al (2014), Joy and Idowu (2014) and Obasi (2015) found that public library and information services generally revolve around community information services, reference services, storytelling services, film show services, reading competition services, career information services, photocopying services, opening hours, online Internet services, lending services, reference services, photocopy services, indexing and abstracting services and bibliographic services. Other services include telephone, recreational and advisory services, current awareness, selective dissemination of information, bookmobiles, referral services, children/school services, computers/Internet/ICT, translation services, user education, outreach and extension programmes, adult literacy programmes, consultancy services, audiovisual services, and packaging and repackaging of information services, among others.…”
Section: Forms Of Information Services Provided By Public Libraries To Rural Dwellers In the Zone Under Studymentioning
confidence: 99%
“…Research on the information needs of high school students in Nigeria has shown that students' primary information literacy needs are related to their studies (Adesoye & Amusa, 2011;Akinola et al, 2013), which force them to deal with complex, unexpected, poorly structured situations (El-Khayat, 2016;Wijaya, 2016). However, as Udofia (2012) points out, the level of information literacy is also closely related to the cultural environment or family background, as confirmed by other studies by Nishikawa and Izuta (2019).…”
Section: Discussionmentioning
confidence: 84%
“…Výzkum informačních potřeb studentů středních škol v Nigerii zaznamenal, že primární potřeby studentů souvisí s jejich studiem (Adesoye & Amusa, 2011;Akinola et al, 2013), ale jak uvádí Udofia (2012), má těsnou souvislost také s kulturním prostředím či rodinným zázemím, což potvrzují i ze zcela jiného kulturního prostředí Nishikawa a Izuta (2019). Jinými slovy, školní prostředí, kulturní život a běžné lidské či občanské prostředí od sebe nemůžeme oddělit ani v abstraktním analytickém nahlédnutí.…”
Section: Diskuseunclassified